Model Fundrising Wakaf di Perguruan Tinggi ‎(Pengalaman UINSU Medan)‎ - Saparuddin Siregar (Jurnal Ilmiah Ekonomi Islam, 2020)
Fundraising of Waqf relatively difficult then fundraising of Zakah. It’s because waqf is not ‎a religious obligation like Zakah. However, it is realized that waqf has great potential to ‎become a tool for improving the economy of the ummah. The aim of this study is to ‎describe the experience of UINSU Medan as an educational institution in ‎collecting the ‎Waqf. This study applies a ‎qualitative approach, ‎with three qualitative methods in data ‎collection: library research, ‎interviews, and data ‎documentation. Open interviews were ‎conducted with ten participants (students, lecturers, and employees). The findings of this ‎study show that the success of Waqf ‎fundraising is based on a mandatory basis, not on a ‎voluntary basis. ‎‎